HUBUNGAN USIA MELAHIRKAN ANAK PERTAMA DENGAN KEJADIAN KANKER PAYUDARA DI RUMAH SAKIT UMUM DAERAH dr. ZAINOEL ABIDIN BANDA ACEH - Meylissa; Diana Lestari (Medic Nutricia : Jurnal Ilmu Kesehatan, 2024)
Cancer remains a significant health issue worldwide, including in Indonesia. Breast cancer is the leading cause of cancer-related deaths among women. At the Dr. Zainoel Abidin Regional General Hospital, there were 287 cases of breast cancer in 2020, with 12 deaths; 175 cases in 2021, with 10 deaths; and 160 cases in 2022, with 8 deaths. This study aims to determine the relationship between family medical history and the incidence of breast cancer at Dr. Zainoel Abidin Regional General Hospital, Banda Aceh. This research is a survey study with a case-control design. The case sample in this study includes women with breast cancer at Dr. Zainoel Abidin Regional General Hospital, Banda Aceh, while the control sample comprises women without breast cancer at the same hospital. A total of 47 cases and 47 controls were selected using Consecutive Sampling. The instrument used in this study was a questionnaire, and data analysis was performed using the Chi-Square test. The results indicate that there is a relationship between the age of having the first child and the incidence of breast cancer. The statistical test yielded a p-value of < 0.002, indicating a significant relationship between the age of having the first child and the incidence of breast cancer. The analysis also produced an Odds Ratio (OR) of 3.938 with a 95% Confidence Interval (CI) of 1.534 – 9.438. In conclusion, there is a relationship between the age of having the first child and the incidence of breast cancer. It is recommended that all women perform Breast Self-Examination (BSE), as breast cancer can still be treated if detected in its early stages